The Role of Adaptive Selling Behavior in Mediating Sales Orientation and Customer Orientation on Salesperson Performance - Citra Amanah; Diana Aqmala; Aries Setiawan (Transpublika Publisher, 2026)
The decline in Mitsubishi Xpander sales indicates problems in sales force performance. Based on preliminary field reports, the suspected problem is related to the suboptimal sales orientation and customer orientation in shaping adaptive sales behaviour. Accordingly, this inquiry endeavors to elucidate the influence of sales orientation and customer orientation on the performance of the Mitsubishi Xpander sales force in Semarang, positioning adaptive sales behaviour as an intervening mechanism. Adopting a quantitatively driven research design, empirical evidence was garnered from 104 purposively selected respondents. The analytical procedure employed Partial Least Squares–Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0. The empirical findings demonstrate that both sales orientation and customer orientation exert a statistically robust and affirmative effect on adaptive sales behaviour, which in turn manifests a significant and positive contribution to sales force performance. Notably, customer orientation, in conjunction with adaptive sales behaviour, emerges as the most potent conduit for enhancing the performance of Mitsubishi Xpander sales personnel within the Semarang context. Customer orientation enables salespeople to understand customer needs and provide appropriate services, while adaptive sales behaviour helps them adjust their approach to different customer characteristics and situations. The findings imply that sales orientation and customer orientation can shape more adaptive sales behaviour, thereby playing a role in driving improvements in sales personnel performance in achieving targets and retaining customers.